PENGARUH LOCUS OF CONTROL DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA DENGAN MODERASI BUDAYA ORGANISASI (Studi pada Dinas Peternakan dan Perikanan Kabupaten Temanggung) - 11.52.02.0106, Mukhlis (Jurnal Mahasiswa Pasca Sarjana, 2013)
This research aims to descrip and analyze the effect of locus of control and job characteristics on employee performance and the effect of locus of control and job characteristics on employee performance organizational culture with moderation. The research located at kabupaten temanggung. Research Sample amount to 115 respondent by using sensus sampling method.Models to be developed during the research are four hypothecal models, which go for the multiple regression analyze and moderation regression analyze method of SPSS analitycal device.The result of research showed that variable of locus of control and job characteristics have a positive and significant influence on employee performance, job characteristic have the most dominant influence on employee performance. Organisational culture can moderate the influence of locus of control on employee performance but organizational culture cannot moderate job characteristics on employee performance. Keywords : locus of control, job characteristic, organizational culture and performance.